Prevalence of antiâC-reactive protein autoantibody and its correlation with disease activity in systemic lupus erythematosus patients at Cipto Mangunkusumo General Hospital - Lusiani, Lusiani; Setiyohadi, Bambang; Sukmana, N; Abdullah, M (Indonesian Rheumatology Association, 2010)
Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease with various underlying mechanisms characterized by autoantibody overproduction. It has been known that mortality and morbidity of SLE was higher in Asian patients compared with white patients. Several studies had showed that C-reactive protein (CRP) has the ability to suspend the progression of SLE through regulatory and clearance pathway, and low level of CRP and high level of anti-CRP antibody has been detected in SLE patients. A question raise whether mortality and morbidity in Asian SLE patients are associated with anti-CRP antibody.Objective: To study the prevalence of anti-CRP antibody and its relationship with disease activity in SLE patients at Cipto Mangunkusumo General Hospital,Jakarta.Methods: This is a cross-sectional study conducted at Cipto Mangunkusumo General Hospital from December 2009 until May 2010. Subjects were SLE patients whowere diagnosed based on the 1982 American College of Rheumatology criteria. Disease activity was measured using the Mexican SLE Disease Activity Index scoringsystem. Anti-CRP antibody assay was performed using the Western blot analysis. Correlation between the presence of anti-CRP antibody and disease activitywas evaluated using the T-test and multivariate logistic regression analysis.Result: Forty SLE patients with a mean age of 31.65 (SD 8.84) were enrolled in the study, 33 of which (82.5%) had positive autoantibody to CRP pentamer. The anti-CRP antibody was signifi cantly correlated (p = 0.024) with disease activity. Conclusions: There was a relatively large proportion of patients with positive anti-CRP antibody among SLE patients in Cipto Mangunkusumo General Hospital. Therewas also a signifi cant correlation between anti-CRP antibody and the disease activity.